Deradikalisasi dan Penanggulangan Terorisme di Indonesia: Telaah Paradigmatik melalui Teori Rekognisi Axel Honneth - Rizal, Januar (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2021)
The development of policies to combat terrorism in Indonesia shows the relationship between counter-terrorism and de-radicalization activities against ex-convicts. Currently, a fundamental and philosophical study of deradicalization is still needed. The views of Dahrendorf’s conflict theory, and Berger & Luckmann’s theory of social reality construction, are seen through a paradigmatic study of critical theory. Axel Honneth’s recognition theory as the third-generation critical theory of the Frankfurt school is used to analyze the phenomenon of deradicalization in countering terrorism in Indonesia. Through the qualitative research format of multi-case instrumental case studies with in-depth interviews and involved observations of ex-convicts who have been able to have social independence, this study finds an emancipatory dialectic space in the phenomenon of deradicalization in Indonesia. The emancipatory dialectic space became a “new engagement” for the phenomenon of deradicalization of the ex-convict in a terrorism case.